Effect of chemical and metallic compounds on biomass, mRNA levels and laccase activity of Phlebia brevispora BAFC 633 - Fonseca, Maria Isabel (2014)
Nine aromatic compounds (caffeic acid, syringaldehyde, vanillic acid, guaiacol, vanillin, sinapic acid, syringol, syringic acid and ferulic acid) and four metallic compounds (CuSO4, AgNO3, MnSO4, and CaCl2) were tested for their ability to increase laccase (Lac) activity in the ligninolytic basidiomycete Phlebia brevispora BAFC 633.The addition of syringaldehyde, syringol, guaiacol, sinapic acid, vanillin, ferulic acid and CuSO4 showed a positive effect on fungal growth; however, it decreased dramatically with the addition of AgNO3 and did not undergo changes in the presence of CaCl2 or MnSO4. Lac activity increased with the addition of all the compounds tested, depending on the concentration and the day of culture. P. brevispora BAFC 633 produced two isoenzymes, a constitutively expressed of 60 kDa and another of 75 kDa expressed upon induction by sinapic acid, MnSO4 or CuSO4. Laccase secretion capacity of Phlebia brevispora BAFC 633 can be increased 27 times higher than the control with the highest levels detected in the presence of 0.3 mM CuSO4 at day 14. The action is affected at pre-transcriptional level regulating at the onset of the process, however it does not rule out the effect at the post-transcriptional and post-translational levels, for which is necessary to deepen in the knowledge of all possible regulation points of gene expression.